2023
DOI: 10.1039/d2nr06676a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen adsorption via charge transfer on vacancies created during surfactant assisted exfoliation of TiB2

Abstract: Titanium diboride (TiB2), a layered ceramic material, comprised of titanium atoms sandwiched in between honeycomb planes of boron atoms, exhibits a promising structure to utilize the rich chemistry offered by the synergy of titanium and boron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 86 publications
(111 reference statements)
1
36
0
Order By: Relevance
“…This is possibly due to the disruption of bonds during milling, which leads to an exposed site of boron that reacts with atmospheric N 2 . We have observed a similar peak for TiB 2 nanosheets obtained via surfactant-assisted exfoliation in another work (Rasyotra et al ) by our research group . In that work, we have presented detailed insights about the chemisorption of N 2 on pristine TiB 2 nanosheets under ambient conditions, which is due to vacancies and the Ti–B synergy.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…This is possibly due to the disruption of bonds during milling, which leads to an exposed site of boron that reacts with atmospheric N 2 . We have observed a similar peak for TiB 2 nanosheets obtained via surfactant-assisted exfoliation in another work (Rasyotra et al ) by our research group . In that work, we have presented detailed insights about the chemisorption of N 2 on pristine TiB 2 nanosheets under ambient conditions, which is due to vacancies and the Ti–B synergy.…”
Section: Resultssupporting
confidence: 76%
“…We have observed a similar peak for TiB 2 nanosheets obtained via surfactant-assisted exfoliation in another work (Rasyotra et al) by our research group. 35 In that work, we have presented detailed insights about the chemisorption of N 2 on pristine TiB 2 nanosheets under ambient conditions, which is due to vacancies and the Ti−B synergy. The second and third daughter peaks correspond to the B−O bonds, which are possibly observed due to the interaction of zirconia balls (ZrO 2 ) with the boron atoms, forming an oxide layer over the material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research efforts over the past few years have been directed toward deriving nanosheets from TiB 2 in both functionalized and minimally functionalized forms. We have shown that nanosheets from TiB 2 can be derived by dissolution and recrystallization, 16 cosolvent-assisted exfoliation, 23 surfactant-assisted exfoliation, 36 and, very recently, mechanical exfoliation. 37 Among these methods, dissolution and recrystallization was our first attempt at exfoliating TiB 2 .…”
Section: ■ Introductionmentioning
confidence: 99%